Arctic tundra fires: natural variability and responses to climate change. Issue 7 (1st September 2015) - Hu, Feng Sheng; Higuera, Philip E; Duffy, Paul; Chipman, Melissa L; Rocha, Adrian V; Young, Adam M; Kelly, Ryan; Dietze, Michael C
Abstract : Anthropogenic climate change may result in novel disturbances to Arctic tundra ecosystems. Understanding the natural variability of tundra‐fire regimes and their linkages to climate is essential in evaluating whether tundra burning has increased in recent years. Historical observations and charcoal records from lake sediments reveal a wide range of fire regimes in Arctic tundra, with fire‐return intervals varying from decades to millennia. Analysis of historical data shows strong climate–fire relationships, with threshold effects of summer temperature and precipitation. Projections based on 21st‐century climate scenarios suggest that annual area burned will approximately double in Alaskan tundra by the end of the century. Fires can release ancient carbon from tundra ecosystems and catalyze other biogeochemical and biophysical changes, with local to global consequences. Given the increased likelihood of tundra burning in coming decades, land managers and policy makers need to consider the ecological and socioeconomic impacts of fire in the Far North.